On Fabric, Feminism and Faulty Legal Systems: Iran’s 1979 Revolution and its Politics of Touch - Amin, Zeena (AUC Knowledge Fountain, 2021)
The intersection of body and state is a fascinating phenomenon of modern-day politics. We are continuously subjected to the ingeniousness with which the ruling classes monitor and regulate our bodies; and most times we are not even aware of it. Whether it is for control over resources or political power and authority, the state uses its institutions and various tools available to it for the purpose of maintaining disciplined, uniform populations that could otherwise threaten prevailing power structures. In particular, the patriarchy has perpetuated the notion that a woman’s body is a specific threat to those prevailing power structures. This thesis engages with states’ use of their legal institutions to subjugate women by controlling their bodies. To demonstrate, the thesis draws on the case of Iran in 1979, when the fall of one power structure led to the rise of another, and the control of revolutionary bodies that could potentially challenge the newly established status-quo became imperative to the state. The thesis takes the hijab law as a chief example to examine the ways in which the Iranian regime touched the bodies of its female subjects following the revolutionary moment in 1979, in order to consolidate its power and ensure methods of perpetuating that touch well into the present day. Against this backdrop of stringent biopolitical agendas, Iranian women continue to draw strength and solidarity in the lived experiences of everyday women, forming a resistance to inspire feminist movements everywhere.